Protein crystallization in a droplet-based microfluidic device: Hydrodynamic analysis and study of the phase behaviour. (14th December 2018) - Ferreira, J.; Castro, F.; Rocha, F.; Kuhn, S.
Graphical abstract: Highlights: Systematic study of protein phase behaviour in a droplet-based microreactor. Numerical prediction of droplet sizes in a flow-focusing geometry. Parametric study to quantify the influence of the droplet volume on nucleation. Parametric study of the influence of the droplet volume on the phase diagram limits. Abstract: This work reports a cheap and easy-to-use droplet-based microfluidic platform for the study of protein crystallization, offering the possibility to characterize the protein phase behaviour, and the effect of volumetric and interfacial phenomena on the crystallization mechanism. We conducted a parametric study supported by comparison with literature data, to quantify the influence of the droplet volume on the thermodynamic (solubility data) and kinetic (metastability data) parameters, using lysozyme as a model protein. Experiments were performed in a tubular microreactor at low Capillary numbers (4.1 × 10 −5 –2.3 × 10 −4 ), resulting in a broad range of droplet sizes. The droplet formation in a flow-focusing geometry was also numerically studied using CFD and a correlation for the droplet size was developed. Subsequently, the lysozyme phase behaviour and the possible mechanisms associated with the nucleation process were evaluated. While crystallization in small volume droplets is usually characterized by a low nucleation probability and correspondingly low number of crystals, we did not observe this in our experiments. A potential explanation for this is the complex and stochastic mechanism of nucleation, including the competition between monomers and oligomers in solution.